Constitution: Between law and politics - Dobryninas, Aleksandras (Politologija, 2025)
In Soviet legal tradition terms "basic law" and "constitution" were treated as synonyms. From the first sight there was no mistake and international constitutional practice has enough examples of this sort: Article Six of the Constitution of the USA describes the constitution as "the supreme law of the land," content of Articles Six and Seven of the Lithuanian Constitution have analogous meaning, etc. However, in Soviet context the identification of constitution and law had another connotation and rather pointed on wishes of communist leaders to administrate society than to respect autonomy of law and basic human rights. Unfortunately, in present Lithuanian legal and political discourses one still can face this uncritical identification of constitution with basic law. In such circumstances, the discussions about political and legal interpretations of constitution are not only of theoretical, but also of practical importance.Political and legal aspects of constitution could be clearly demonstrated in the light of ideas presented by Aristotle in his famous Politics. For him, constitution is the set of principles of political organization of society. Due to this fact, constitution differs from law and everyday political decisions that have to fit the existing political order. In their turn, laws differ from political decisions as more stable and less dependent on political conjuncture matter. Although Aristotle's political and legal ideas do not meet modern requirements for democratic constitution, one can learn some useful lessons from his teaching. The most important and actual of them is that short-term political interests do not have to influence legislative procedure and destabilize constitutional order. The remedy for frequent constitutional changes one has to seek in proper education of political elite that should consist not of nice and good people, but of perfect citizens, who would be able to govern and at the same time obey orders.Contemporary Lithuanian Constitution is a product of recent radical political changes that on the one hand, restore historical justice, and on the other hand, establish just political organization of modern society—a democratic republic. Unfortunately, due to the lack of democratic tradition, Lithuania's orientation to the western-type political order was not based on solid "democratic instinct" (V. Kavolis) of society; rather it was a decision "in advance" without clear understanding of structure and institutional principles of free and open society. In this context, countless attempts of Lithuanian politicians to change the constitution or to make amendments in constitutional articles could be evaluated as neglecting the political significance of the constitution, as well as deeds destabilizing the new democratic order. Instead of political attack on constitutional text, one has to strengthen judicial interpretative procedure that could make the existing written constitution clearer and more fitted to present and future needs of Lithuanian society.
Keywords: -